FinnWordNet och kulturbundna ord - Martola, Nina (LexicoNordica, 2011)
In this paper I analyze the beta version of the Finnish WordNet from a societal and cultural point of view. FinnWordNet has been created through translation of the Princeton WordNet (Lindén & Carlson 2010). Certain lexicographical problems are to be expected due to the method. Essential terms referring to Finnish society structure and Finnish culture cannot be found in the present FinnWordNet. The English definitions for words that can be found are not adequate from a Finnish viewpoint and the concept hierarchies are only partly relevant. Constructing a WordNet is a laborious process and starting by translating is not a bad alternative. The linking to the English WordNet comes ‘for free’. If the work had started by building up an independent WordNet for Finnish the linking process would have been very time-consuming. But pure word translation from L1 to L2 without any supplementing work does, of course, not result in an adequate description of the target language L2.